1999
DOI: 10.1093/jac/43.suppl_1.117
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and oral mono- or combination-therapy in the treatment of severe infections: ciprofloxacin versus standard antibiotic therapy

Abstract: Five hundred and forty patients with severe infection were enrolled in a multicentre, prospective, randomized, non-blinded study to compare the efficacy and safety of i.v. ciprofloxacin with i.v. standard therapy. Five hundred and thirty-one patients received at least one dose of study drug for pneumonia (310), septicaemia (112) or skin and skin structure infection (109). Intravenous ciprofloxacin (400 mg, every 8 h) or i.v. ciprofloxacin (400 mg, every 8 h) plus a beta-lactam were compared with a standard mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…Monotherapy with cefditoren pivoxil achieved clinical cure rates, microbiological cure rates, and overall eradication rates comparable to those associated with amoxicillin/clavulanate [72]. Ciprofloxacin, as monotherapy or in combination with a b-lactam, showed efficacy similar to that of standard monotherapy with a b-lactam or standard combination therapy with an aminoglycoside plus a b-lactam [73].…”
Section: Pneumoniamentioning
confidence: 81%
“…Monotherapy with cefditoren pivoxil achieved clinical cure rates, microbiological cure rates, and overall eradication rates comparable to those associated with amoxicillin/clavulanate [72]. Ciprofloxacin, as monotherapy or in combination with a b-lactam, showed efficacy similar to that of standard monotherapy with a b-lactam or standard combination therapy with an aminoglycoside plus a b-lactam [73].…”
Section: Pneumoniamentioning
confidence: 81%
“…Reasons for exclusion included the following: (1) not randomized ( ), (2) small sample size ( ), (3) used quin-n p 25 n p 5 olones not commercially available ( ), (4) community-n p 4 acquired pneumonia study rather than a trial of NP ( ), n p 3 (5) not comparator controlled ( ), and (6) lost 120% of n p 3 cohort to follow-up ( ). n p 1 The 5 studies included in the final evaluation comprised a total of 1186 patients [17][18][19][20][21]. The median quality score (as defined by Jadad et al [16]) was 6 (range, 5-7).…”
Section: Resultsmentioning
confidence: 99%
“…Only the investigation conducted by Fink et al [17] was double blind; the remainder were open-label studies. Four of the 5 trials used ciprofloxacin [17][18][19][20], but that by West et al focused on levofloxacin [21]. All the trials of ciprofloxacin used doses Because "positive" trials (i.e., those that detect a difference associated with an intervention) are more likely to be published, it is important, when performing a meta-analysis, to search for "negative" trials (i.e., those that fail to note a difference between control and intervention groups).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, five studies, of which four enrolled only patients with severe community-acquired or nosocomial pneumonias, showed that fluoroquinolones (ciprofloxacin, four studies; levofloxacin, one study) were as efficacious as ␤-lactam antibiotics (imipenem in four studies; various ␤-lactams with or without an aminoglycoside in one study) for the treatment of patients with severe sepsis caused predominantly by Gramnegative bacteria (Table 2) (56,105,106,109,110). Of note, a large number of patients (ranging between 250 and 400) were randomized in three of the four pneumonia studies.…”
Section: Single-agent Antibiotic Therapiesmentioning
confidence: 99%